Determinação do risco de erosão com utilização de um sistema de informações geográficas - ARAUJO, QUINTINO REIS DE; MOTTA, LUIZ PACHECO; SALOMÃO, ANA LUISA FAGUNDES; BRITES, RICARDO SEIXAS (Revista Ceres, 2015)
.